Altered Amplitude of Low-frequency Fluctuations in Early and Late Mild Cognitive Impairment and Alzheimer's Disease - Liang, Peipeng; Xiang, Jie; Liang, Hong; Qi, Zhigang; Li, Kuncheng; Alzheimer’s Disease NeuroImaging Initiative (Current Alzheimer Research, 2014)
Purpose: Previous studies have shown that the strength of the low frequency fluctuation in the medial-line brain areas are abnormally reduced in mild cognitive impairment (MCI) and Alzheimer’s disease (AD) patients. The purpose of this study was to explore the functional brain changes in early MCI (EMCI) and late MCI (LMCI) patients by measuring the amplitude of the blood oxygenation level dependent (BOLD) functional MRI (fMRI) signals at rest. Materials and methods: 35 elderly normal controls (NC), 24 EMCI, 29 LMCI, and 14 AD patients from the Alzheimer’s Disease Neuroimaging Initiative (ADNI2) were included in this study. Resting state fMRI and 3D structural MRI data were acquired. The spatial patterns of spontaneous brain activity were measured by examining the amplitude of low-frequency fluctuations (ALFF) of BOLD signal during rest. A one-way analysis of variance (ANOVA) was then performed on ALFF maps, with age, sex and regional atrophy as covariates. Results: There were widespread ALFF differences among the four groups. As compared with controls, AD, LMCI and EMCI patients showed decreased ALFF mainly in the posterior cingulate cortex, precuneus, right lingual gyrus and thalamus (with a linear trend: NC>EMCI>LMCI>AD), while there was increased activity in the right parahippocampal gyrus (with a linear trend: NC<EMCI<LMCI<AD). Additionally, we also showed that many regions with ALFF changes had significant correlations with the cognitive performance as measured by mini-mental state examination scores (MMSE) and the emotion states as measured by Geriatric Depression Scale (GD scale) for EMCI, LMCI and AD patients, but not for controls. Conclusion: Our results indicated that the significantly altered ALFF activities can be detected at EMCI stage, independent of age, sex and regional atrophy. The present study thus suggests ALFF abnormalities as a potential biomarker for the early diagnosis of AD and further provides insights into biological mechanisms of the diseases.
Keywords: early mild cognitive impairment (EMCI)